2021
DOI: 10.26508/lsa.202000992
|View full text |Cite
|
Sign up to set email alerts
|

Gametic specialization of centromeric histone paralogs in Drosophila virilis

Abstract: In most eukaryotes, centromeric histone (CenH3) proteins mediate mitosis and meiosis and ensure epigenetic inheritance of centromere identity. We hypothesized that disparate chromatin environments in soma versus germline might impose divergent functional requirements on single CenH3 genes, which could be ameliorated by gene duplications and subsequent specialization. Here, we analyzed the cytological localization of two recently identified CenH3 paralogs, Cid1 and Cid5, in Drosophila virilis using specific ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 64 publications
(98 reference statements)
0
10
3
Order By: Relevance
“…Overall, our analyses reveal that hcp-3 has duplicated at least ten independent times within Caenorhabditis species. In contrast to plants, Drosophila , and mosquito species (Kursel and Malik 2017; Kursel, et al 2020; Kursel, et al 2021), we observed only a few cases of hcp-3L paralogs that are shared across two or three Caenorhabditis sister species, although this may partly reflect density of species sampling in these different taxonomic groups. Our findings suggest that most of the hcp-3L paralogs we have found are relatively young, if the relative ages of Caenorhabditis and Drosophila species analyzed are comparable (Cutter 2008).…”
Section: Resultscontrasting
confidence: 80%
See 3 more Smart Citations
“…Overall, our analyses reveal that hcp-3 has duplicated at least ten independent times within Caenorhabditis species. In contrast to plants, Drosophila , and mosquito species (Kursel and Malik 2017; Kursel, et al 2020; Kursel, et al 2021), we observed only a few cases of hcp-3L paralogs that are shared across two or three Caenorhabditis sister species, although this may partly reflect density of species sampling in these different taxonomic groups. Our findings suggest that most of the hcp-3L paralogs we have found are relatively young, if the relative ages of Caenorhabditis and Drosophila species analyzed are comparable (Cutter 2008).…”
Section: Resultscontrasting
confidence: 80%
“…Conflicting evolutionary selective pressures on CenH3 between these functions (e.g., mitotic versus meiotic, conserved versus rapidly evolving) could be resolved by gene duplication, which allows the duplicate (paralog) and ancestral genes to specialize in different functions (Gallach and Betrán 2011). Indeed, CenH3 genes have also undergone repeated gene duplications not just in plant but also in several animal species including cows, fruit flies, mosquitoes, and nematodes (Li and (Kursel, et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ‘out-of-testis’ hypothesis predicts that the male germline provides an initial ‘gene nursery’ for evolutionary innovation, with diversification subsequently broadening its expression profile ( Assis and Bachtrog, 2013 ; Vinckenbosch et al, 2006 ; Nyberg and Carthew, 2017 ). Recent studies of histone variants, which were originally thought to be ‘testis-specific’ in Drosophila and mammals, based on RT-PCR data, demonstrated that their expression and function also extends to females ( Kursel et al, 2021 ; Molaro, 2020 ). Similarly, Umbrea, which is highly testis-enriched, is required for chromosome segregation more broadly ( Ross et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%